Portal vein embolization stimulates tumour growth in patients with colorectal cancer liver metastases - Simoneau, Eve; Aljiffry, Murad; Salman, Ayat; Abualhassan, Nasser; Cabrera, Tatiana; Valenti, David; El Baage, Arwa; Jamal, Mohammad; Kavan, Petr; Al-Abbad, Saleh; Chaudhury, Prosanto; Hassanain, Mazen; et al. (HPB (Oxford, England), 2012)
Portal vein embolization (PVE) can facilitate the resection of previously unresectable colorectal cancer (CRC) liver metastases. Bevacizumab is being used increasingly in the treatment of metastatic CRC, although data regarding its effect on post-embolization liver regeneration and tumour growth are conflicting. The objective of this observational study was to assess the impact of pre-embolization bevacizumab on liver hypertrophy and tumour growth. Computed tomography scans before and 4weeks after PVE were evaluated in patients who received perioperative chemotherapy with or without bevacizumab. Scans were compared with scans obtained in a control group in which no PVE was administered. Future liver remnant (FLR), total liver volume (TLV) and total tumour volume (TTV) were measured. Bevacizumab was discontinued ≥4weeks before PVE. A total of 109 patients and 11 control patients were included. Portal vein embolization induced a significant increase in TTV: the right lobe increased by 33.4% in PVE subjects but decreased by 34.8% in control subjects (P < 0.001), and the left lobe increased by 49.9% in PVE subjects and decreased by 33.2% in controls (P= 0.022). A total of 52.8% of the study group received bevacizumab and 47.2% did not. There was no statistical difference between the two chemotherapy groups in terms of tumour growth. Median FLR after PVE was similar in both groups (28.8% vs. 28.7%; P= 0.825). Adequate liver regeneration was achieved in patients who underwent PVE. However, significant tumour progression was also observed post-embolization.